2018
DOI: 10.1111/cod.13040
|View full text |Cite
|
Sign up to set email alerts
|

Is a specific eyelid patch test series useful? Results of a French prospective study

Abstract: In French patients, testing for EACD with the extended baseline series and personal products, also including ROATs and use tests, appears to be adequate, considering the currently relevant positive test reactions. The regular addition of an eyelid series does not seem to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…The high rate of fragrance allergy in this cohort (30.4%) echoes the results from multiple other studies that found fragrances to be major agents in eyelid ACD (Amin and Belsito, 2006, Ayala et al, 2003, Ockenfels et al, 1997, Shah et al, 1996, Valsecchi et al, 1992). High rates of contact sensitization to hydroperoxides of linalool and limonene reflect the high prevalence in the literature (Assier, 2018, Dittmar and Schuttelaar, 2019, Nath et al, 2017) and reinforce these as high-risk allergens. Although evidence exists that linalool and limonene may frequently cause irritant reactions (Assier, 2018), we found four of six reactions to be more pronounced at 5 days than at 2 days, which supports a diagnosis of ACD.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The high rate of fragrance allergy in this cohort (30.4%) echoes the results from multiple other studies that found fragrances to be major agents in eyelid ACD (Amin and Belsito, 2006, Ayala et al, 2003, Ockenfels et al, 1997, Shah et al, 1996, Valsecchi et al, 1992). High rates of contact sensitization to hydroperoxides of linalool and limonene reflect the high prevalence in the literature (Assier, 2018, Dittmar and Schuttelaar, 2019, Nath et al, 2017) and reinforce these as high-risk allergens. Although evidence exists that linalool and limonene may frequently cause irritant reactions (Assier, 2018), we found four of six reactions to be more pronounced at 5 days than at 2 days, which supports a diagnosis of ACD.…”
Section: Discussionmentioning
confidence: 65%
“…High rates of contact sensitization to hydroperoxides of linalool and limonene reflect the high prevalence in the literature (Assier, 2018, Dittmar and Schuttelaar, 2019, Nath et al, 2017) and reinforce these as high-risk allergens. Although evidence exists that linalool and limonene may frequently cause irritant reactions (Assier, 2018), we found four of six reactions to be more pronounced at 5 days than at 2 days, which supports a diagnosis of ACD. The other two reactions experienced a stable or decrease response.…”
Section: Discussionmentioning
confidence: 65%
“…70 In seven studies in which patients with eyelid dermatitis or periorbital dermatitis were patch tested with MP, frequencies of sensitization ranged from 1.7% to 17%, but in five of the seven studies, the frequency was <7%. [72][73][74][75][76][77][78] In three investigations in which relevance was addressed, rates of relevant reactions were 43%, 77 58%, 78 and 75%, 74 but the culprit products were not mentioned. In four studies with a control group, the frequency of sensitization to MP was significantly lower than in routine testing.…”
Section: Relevance and Causative Productsmentioning
confidence: 99%
“…Identification of ACD as the most frequent cause of eyelid dermatitis has been well established, especially in the dermatologic literature. 4,8,[12][13][14][15] Eye care providers are quick to point to topical ophthalmic medications as potential ACD triggers. However, ACD is often misdiagnosed, or ophthalmologists and optometrists may be unsure of therapeutic options if patients fail to improve despite avoidance of ophthalmic medications.…”
Section: Introductionmentioning
confidence: 99%